Gambaran Evaluasi Discharge Planning Pada Pasien Hemodialisa - Afrida, Maryudella Afrida; Nurwidiyanti, Erika; Jennifa, Jennifa (Universitas Tribhuwana Tunggadewi, 2023)
Fluid management adherence is a majority problem for hemodialysis patients. Nurse discharge planning is expected to solve this problem. This study aims to describe the evaluation of discharge planning in hemodialysis patients at Panembahan Senopati Hospital, Yogyakarta. This research is a quantitative descriptive study. The population in this study was 261 people. The purposive sampling was used in the 38 chronic renal failure patients who underwent hemodialysis at Panembahan Senopati Hospital, Bantul. The univariate analysis was performed to obtain the frequency distribution on gender, age, marital status, education, employment status, and length of time undergoing hemodialysis. Participants were completed with evaluation sheets and structured interviews. The characteristics of the respondents were male and female (50% each), aged 26-35 years old (36.8%), (79%) did not work, underwent hemodialysis 1-3 years (57.8 %), and half of the respondents (47.1%) had senior high school education. The implementation of nurse discharge planning included the good category of medication (10.5%), treatment (39.5%), health promotion (26.3%), and diet (47.4%). But the finding that discharge education was performed either the patient asks or if there are abnormal clinical/laboratory results only. It concluded that the implementation of discharge planning is deficient. Additional participation and performing further research related to hemodialysis patients confidence and adherence in supporting discharge planning was strongly recommended.